Performance-based assessment for elementary school students' fundamental motor skills in balance, locomotor, and manipulative movements - Wibowo, Cahyo; Putra, Kukuh Pambuka; Nopiyanto, Yahya Eko; Dese, Dennys Christovel; Pradibya, Aguch Vergianata (Bima Loka: Journal of Physical Education, 2025)
Highlighting the importance of fundamental motor skills encompassing balance, locomotor, and manipulative abilities in the physical development of elementary school children. This study aims to ascertain and provide a better understanding of holistic fundamental motor skills, aiding in identifying children needing continuous intervention. This quantitative descriptive study employs a cross-sectional approach involving 310 respondents of elementary school students aged 7 to 9 years old. The research instrument comprises an assessment rubric with performance observations encompassing eleven types of fundamental motor skills. Ideal mean formula and ideal standard deviation are utilized to analyze data regarding the proficiency levels of each motor skill category. Additionally, an Independent Sample t-test is employed to ascertain the data differences among elementary school students based on gender. The research findings indicate that the elementary school students' fundamental motor skills have an average performance assessment mean of 32.14 (36.12%), with the majority falling into the "good" category. The average performance score of male students is higher than that of female students, with a mean of 30.32 and a standard deviation of 3.590, while the average performance score of female students is 28.48, with a standard deviation of 3.208. They explain the variation in motor skills among elementary school students aged 7 to 9. Most students exhibit proficient skills, although some fall into the unsatisfactory motor skill category. On average, male students demonstrate higher motor skills compared to female students.